The Occurrence of Code Mixing in Indonesian Girl Magazine Kawanku - Irwan Rohardiyanto (BUANA GENDER : Jurnal Studi Gender dan Anak, 2017)
This research explains about the mixed code that occurs in complex society especially for daily conversation of young women. The purpose of this study is to get a description of the mixed code in the magazine Kawanku, which is to get an idea of how and what factors mix the Indonesian slang code that appears in my magazine. This study used descriptive qualitative method. The findings of the research are the use of foreign languages by Indonesians and they prefer to use non-standard language instead of standard language. The author gets several factors that influence the interference of the code. It is important for Indonesian teenagers to use standard Indonesian when they communicate with each other to preserve their language. This study also aims to make the language study institutions make Indonesian terms in its policy.